STRATEGI PEMASARAN SYARI’AH PADA BMT AL-AMANAH DALAM MENINGKATKAN MODAL DAN PENYALURAN PEMBIAYAAN - Muhamad Subhan (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2018)
This research is a field research conducted at the Al-Amanah BMT in Jambi City. Data collection techniques in this study use methods of observation, interviews, and documentation. The formulation of the problem in this study is how the marketing strategy carried out by BMT Al-Amanah in increasing capital and financing distribution, the constraints faced and efforts to overcome these obstacles. This study produces three conclusions, namely: (1) the marketing strategy carried out by BMT Al-Amanah Jambi City in increasing capital and financing distribution is by determining the market segmentation of products and services, conducting marketing activities in accordance with the target market, as well as positioning and mixing concepts. marketing; (2) the constraints faced include the lack of human resources who are competent in their fields, the source of funds as limited capital, and the existence of tight competition with other financial institutions. (3) efforts made to overcome obstacles are by improving the quality of human resources, continuing to strive to be able to increase the number of customers, and increase capital and financing distribution through promotion and introducing the BMT financial system to the wider community.